What is an Ethnographic Archive an Archive of? A Telling Case of Challenges in Exploring Developing Interdisciplinary Programs in Higher Education - Green, Judith; Chian, Monaliza; Stewart, Ethny; Couch, Stephanie (Acta Paedagogica Vilnensia, 2017)
This paper seeks to (re)think what constitutes records within an ethnographic archive by making visible the challenges that our external IE team faced as we entered the records archived by the internal IE team that we were invited to support in the documentation and analysis of a developing Instructional Development Project. Although both teams shared a common conceptual logic-of-inquiry – Interactional Ethnography – It became evident that there were limits to certainty (Green & Baker 2007) that led us to (re)examine why some particular records were archived and what they were records of.